2021
DOI: 10.1177/20662203211024105
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring: Can you get too much of a ‘good thing’? Proposing enhancements to the ‘effectiveness framework’ the England and Wales Prison and Probation Service

Abstract: Opt-in, open-ended mentoring for people with convictions, allowing them to dip in and out of services without sanction arguably offers a service configuration to match the paradigm of the zig-zag, nomadic desistance journey. Balancing supporting individual’s agency while avoiding fostering dependency is tricky. What are the conditions which support the former and avoid the latter? We aim to answer this question by drawing on the lived experience of mentees and mentors collected during the evaluation of a mento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It may be that having an experiential peer could become that very hook. In an evaluation of a mentoring scheme, capitalising on lived experiences of mentees and mentors, Wong and Horan (2021) found that supporting individual agency, whilst avoiding dependency is a tricky balance within this framework. It was suggested that the balance towards dependency is something that is unlikely to be effective and empower clients.…”
Section: Limitations Of Experiential Peersmentioning
confidence: 99%
“…It may be that having an experiential peer could become that very hook. In an evaluation of a mentoring scheme, capitalising on lived experiences of mentees and mentors, Wong and Horan (2021) found that supporting individual agency, whilst avoiding dependency is a tricky balance within this framework. It was suggested that the balance towards dependency is something that is unlikely to be effective and empower clients.…”
Section: Limitations Of Experiential Peersmentioning
confidence: 99%